Impact of different trace elements on metabolic routes during heterotrophic growth of C. ljungdahlii investigated through online measurement of the carbon dioxide transfer rate. (26th April 2022) - Mann, Marcel; Effert, Darina; Kottenhahn, Patrick; Hüser, Aline; Philipps, Gabriele; Jennewein, Stefan; Büchs, Jochen
Abstract: Synthesis gas fermentation using acetogenic clostridia is a rapidly increasing research area. It offers the possibility to produce platform chemicals from sustainable C1 carbon sources. The Wood‐Ljungdahl pathway (WLP), which allows acetogens to grow autotrophically, is also active during heterotrophic growth. It acts as an electron sink and allows for the utilization of a wide variety of soluble substrates and increases ATP yields during heterotrophic growth. While glycolysis leads to CO2 evolution, WLP activity results in CO2 fixation. Thus, a reduction of net CO2 emissions during growth with sugars is an indicator of WLP activity. To study the effect of trace elements and ventilation rates on the interaction between glycolysis and the WLP, the model acetogen Clostridium ljungdahlii was cultivated in YTF medium, a complex medium generally employed for heterotrophic growth, with fructose as growth substrate. The recently reported anaRAMOS device was used for online measurement of metabolic activity, in form of CO2 evolution. The addition of multiple trace elements (iron, cobalt, manganese, zinc, nickel, copper, selenium, and tungsten) was tested, to study the interaction between glycolysis and the Wood ljungdahl pathway. While the addition of iron(II) increased growth rates and ethanol production, added nickel(II) increased WLP activity and acetate formation, reducing net CO2 production by 28%. Also, higher CO2 availability through reduced volumetric gas flow resulted in 25% reduction of CO2 evolution. These online metabolic data demonstrate that the anaRAMOS is a valuable tool in the investigation of metabolic responses i.e. to determine nutrient requirements that results in reduced CO2 production. Thereby the media composition can be optimized depending on the specific goal.